Respiratory Viral Infections and Infection Prevention Practices Among Women With Acute Respiratory Illness During Delivery Hospitalizations During the 2019–2020 Influenza Season. (25th May 2021) - Dawood, Fatimah S; Varner, Michael; Munoz, Flor; Stockwell, Melissa S; Suyama, Joe; Li, De-Kun; Tita, Alan; Mathias, Leigh; Shakib, Julie H; Piedra, Pedro A; Gyamfi-Bannerman, Cynthia; Weissman, Alexandra; et al.
Abstract: Background: We conducted a cross-sectional study of pregnant women with acute respiratory illness during delivery hospitalizations during influenza season to describe clinical testing for respiratory viruses and infection prevention practices. Methods: Women had nasal swabs tested for influenza and other respiratory viruses. Among 91 enrolled women, 22 (24%) had clinical testing for influenza. Results: Based on clinical and study testing combined, 41 of 91 (45%) women had samples positive for respiratory viruses. The most common virus was influenza (17 of 91, 19%); 53% (9 of 17) of influenza virus infections were identified through study testing alone. Only 16% of women were on droplet precautions. Conclusions: Peripartum respiratory infections may be underrecognized. Abstract : In this study, half of pregnant women with acute respiratory illness during delivery hospitalizations had respiratory viral infections based on clinical and study testing, but only 16% were on droplet precautions. Peripartum respiratory infections during influenza season may be underrecognized.